The Key Drivers Of Green Hrm Practices And Sustainable Performance: The Roles Of Environmental Orientation And Organizational Innovativeness In The Malaysian Manufacturing Industry - Muniandi, Taleselvi (2021)
This study was conducted among ISO 14001 certified manufacturing sector with the aim to examine the key drivers that induce the adoption and the outcomes of its implementation to the sustainable performance. This study also sought to ascertain the mediating effect of environmental orientation and the moderating effect of organizational innovativeness on the adoption of GHRM practices.